Eficiência lactacional de porcas com diferentes ordens de parto - Felin, Fernanda Pivotto (2017)
The objective of this study was to evaluate the effect of the order of delivery on the efficiency of lactation of pigs. Sixty-six sows with birth orders between 3 and 5 were selected. The weight variation of the females, from calving to weaning, daily feed intake and backfat thickness were evaluated. The variables measured and estimated in the piglets were number of piglets born alive and dead, weight of litters at birth, after homogenization and weekly until weaning. There were no differences (P> 0.05) between the orders of delivery (OP) for the variation of the weight of the sows during lactation. Feed intake and energy intake were not influenced (P> 0.05) by OP. There was no difference (P> 0.05) between POs for birth weight and initial litter weight. OP five sows had litters with energy retention of 1.42 Mcal / d higher than three OP litters. The energy input had no significant difference (P> 0.05) in relation to the OPs. However, the energy output had influence (P <0.05) of the OPs, four OPs and five had higher energy output means than three OPs. OP four and five nuts were more efficient than three OP nuts. The lactate efficiency was 75.08% for OP four and 72.25% for OP five, values higher than OP three, which had efficiency of 53.84%. Labor order three sows show lower lactational efficiency than four and five calving order sows.